Study on the Influence of UAV Wingtip Connection on Ceiling and Endurance - Wei Zhou; Peiyang Ma; Qiuyan Wang; Xueqian Shi; Kaixuan Liu (Global Journals of Research in Engineering, 2023)
The cluster UAVs have developed rapidly in recent years with the advantages of low cost expandability and high reliability However due to their small size they have the shortages of range and flight time Wingtip connection technology as an important way to increase the range and flight time of fixed-wing cluster UAVs has also developed rapidly in recent years From the theoretical analysis it is concluded that the wingtip connection can effectively improve the aerodynamic characteristics of fixed-wing UAVs and the conclusions are validated by vortex lattice method simulation Based on this the influence of the number of units on the flight performance of the combination is analysed theoretically As the number of units increases the combination can have higher ceiling larger range and longer flight time